2023
DOI: 10.1039/d2ta07747g
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature sintering characteristics and electrical properties of Ca- and Bi-doped Li7La3Zr2O12 electrolyte containing Li3BO3 additive

Abstract: i7La3Zr2O12 (LLZ) is one of the most promising Li-ion solid electrolytes for all-solid-state Li-ion batteries. To achieve low interfacial resistance between LLZ and the active materials, low-temperature sintering is required....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 79 publications
0
17
1
Order By: Relevance
“…This phenomenon also occurred in the LLZ–CaBi/Li 3 BO 3 systems synthesized with the stoichiometric composition in our previous study. 15 These results suggest that the Li–Ca–Bi–O liquid phase containing Ca and Bi was formed selectively and remained at the grain boundaries during the sintering process.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This phenomenon also occurred in the LLZ–CaBi/Li 3 BO 3 systems synthesized with the stoichiometric composition in our previous study. 15 These results suggest that the Li–Ca–Bi–O liquid phase containing Ca and Bi was formed selectively and remained at the grain boundaries during the sintering process.…”
Section: Resultsmentioning
confidence: 85%
“…Our group previously reported that co-doping with Ca and Bi signicantly lowered the sintering temperature by forming a Li-Ca-Bi-O liquid phase with a low melting temperature. 15 For instance, we achieved a relative density of 89% and a Li-ion conductivity of 3 × 10 −4 S cm −1 aer sintering at only 750 °C by using Ca-Bi co-doped LLZ and Li 3 BO 3 as sintering aids. However, this Li-ion conductivity is still below the value required for practical use in high-performance solid-state batteries.…”
Section: Introductionmentioning
confidence: 94%
“…successfully decreased the sintering temperature of LLZ to 750 °C by doping Ca and Bi and the addition of Li 3 BO 3 . [ 56 ] The ASSLB using this solid electrolyte exhibited good capacity retention of 92.8% at the 40th cycle. Another idea is a flexible cathode layer by introducing “soft” buffer materials that would absorb the active materials’ volume change.…”
Section: Resultsmentioning
confidence: 99%
“…Table S1, Supporting Information, compares the battery performances of the garnet-based ASSBs/ASSLBs in this work and those reported in the literature. [30,32,[34][35][36]55,56] The variety of the test conditions might cause confusion; however, here we compare the performance from the viewpoint of the large-scale batteries. An areal capacity of 3 mAh cm −2 or higher values would be required for practical application.…”
Section: Cells After the Optimizationmentioning
confidence: 99%
“…Elemental substitution is an effective material design strategy for reducing the LLZ sintering temperature, as it can promote the formation of a liquid phase at lower temperatures; this liquid phase should exhibit good wettability against LLZ particles and dissolve part of the LLZ particles, as established in our previous study. 29 Low-melting-point oxides exhibit a low dissociation energy with respect to oxygen. According to Sun, As 5+ and Sb 5+ are pentavalent elements with lower dissociation energies than Zr 4+ .…”
Section: Introductionmentioning
confidence: 99%